Mortalitas Hama Gudang Tribolium castaneum dan Susut Bobot Pada Beras dan Jagung Dalam Bentuk Utuh, Patah, dan Tepung - Alda Vania Augusta; Lutfi Afifah; Tatang Surjana; Sudarti Sudarti (AGRICA, 2023)
Tribolium castaneum is one of stored pests with vast host against stored commodites. The purpose of this research is to know the survivability of T. castaneum and weight loss on rice and corn in the shape of whole grain, broken grain, and flour. This research used single factor Completely Randomized Design (CRD) consisting of 7 treatments with 4 replications: A (control), B (whole grain of rice), C (broken grain of rice), D (rice flour), E (whole grain of corn), F (broken grain of corn). G (corn flour). The observed variables were temperature and humidity, adult mortality, and feed weight loss. The results showed the differences of feed did not give significant effect on T. castaneum mortality but has siginificant effect on feed weight loss. Corn flour has the most weight loss by 8,50grams. This conclude that T. castaneum has high comsumption activity on corn flour.